Synthesis and characterization of metal nanoparticles by pulsed laser ablation in liquid media (PLAL) - Mendivil Palma, María Isabel (2015)
Nanotechnology is an important topic that implies design, fabrication and application of nanostructures or nanomaterials, and the fundamental understanding of the relationships between physical properties or phenomena and material dimensions [1]. The recent advances in their synthesis methods, characterization techniques and applications have been of great utility. Another important aspect of nanotechnology is the miniaturization of current and new instruments, sensors and machines. We can find their applications in a great variety of areas as nanoscale electronics and optics, nanobiological systems, nanomedicine, technology, biology, disease treatments, etc. Therefore requires contribution from multidisciplinary teams of physicists, chemists, materials scientists, engineers, molecular biologists, pharmacologists, etc. In this thesis we report an easy, fast, alternative-novel and one-step method for the preparation of pure and stable (in some cases) noble metal nanoparticles, viz Pulsed Laser Ablation in liquid media; this method presents significant advantages over chemical routes as: pure metal nanoparticles production, less aggregation, non-vacuum requirements, non-toxic agents are required, size and shape tunability, between others. Pulsed laser ablation in liquid media will be described in detail in the next part,